Welfare to Temporary Work: Implications for Labor Market Outcomes - Carolyn J. Heinrich; Peter R. Mueser; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2002)
Recent welfare reforms are prompting some state and local welfare agencies to use temporary help service firms to help place welfare recipients into jobs. Concerns have arisen that these jobs are more likely to pay low wages, provide fewer benefits, and offer less stability. We explore the effects of temporary help firms on the labor market outcomes of welfare recipients by looking at the characteristics of welfare recipients who go to work for temporary service firms and by examining their subsequent employment and welfare dynamics. We find that although welfare recipients who go to work for temporary help service firms have lower initial wages they experience faster subsequent wage growth. Two years later, their wages are only slightly below workers who initially had jobs in other sectors, and they are no more likely to be unemployed and are only slightly more likely to remain on welfare.
Keywords: J4; J0; I3; 330; temporary help; welfare; Leiharbeit; Wirtschaftspolitische Wirkungsanalyse; Sozialhilfeempfänger; Einkommen; Schätzung; Vereinigte Staaten